The Secretome of Phanerochaete chrysosporium and Trametes versicolor Grown in Microcrystalline Cellulose and Use of the Enzymes for Hydrolysis of Lignocellulosic Materials - Machado, Angela S.; Valadares, Fernanda; Silva, Tatiane F.; Milagres, Adriane M. F.; Segato, Fernando; Ferraz, André (Frontiers in Bioengineering and Biotechnology, 2020)
The ability of white-rot fungi to degrade polysaccharides in lignified plant cell walls makes them a suitable reservoir for CAZyme prospects. However, to date, CAZymes from these species are barely studied, which limits their use in the set of choices for biomass conversion in modern biorefineries. The current work joined secretome studies of two representative white-rot fungi, Phanerochaete chrysosporium and Trametes versicolor, with expression analysis of cellobiohydrolase (CBH) genes, and use of the secretomes to evaluate enzymatic conversion of simple and complex sugarcane-derived substrates. Avicel was used to induce secretion of high levels of CBHs in the extracellular medium. A total of 56 and 58 proteins were identified in cultures of P. chrysosporium and T. versicolor, respectively, with 78-86% of these proteins corresponding to plant cell wall degrading enzymes (cellulolytic, hemicellulolytic, pectinolytic, esterase, and auxiliary activity). CBHI predominated among the plant cell wall degrading enzymes, corresponding to 47% and 34% of the detected proteins in P. chrysosporium and T. versicolor, respectively, which confirms that Avicel is an efficient CBH inducer in white-rot fungi. The induction by Avicel of genes encoding CBHs (cel) was supported by high expression levels of cel7D and cel7C in P. chrysosporium and T. versicolor, respectively. Both white-rot fungi secretomes enabled hydrolysis experiments at 10 FPU/g substrate, despite the varied proportions of CBHs and other enzymes present in each case. When low recalcitrance sugarcane pith was used as a substrate, P. chrysosporium and T. versicolor secretomes performed similarly to Cellic® CTec2. However, the white-rot fungi secretomes were less efficient than Cellic® CTec2 during hydrolysis of more recalcitrant substrates, such as acid or alkaline sulfite-pretreated sugarcane bagasse, likely because Cellic® CTec2 contains an excess of CBHs compared with the white-rot fungi secretomes. General comparison of the white-rot fungi secretomes highlighted T. versicolor enzymes for providing high glucan conversions, even at lower proportion of CBHs, probably because the other enzymes present in this secretome and CBHs lacking carbohydrate-binding modules compensate for problems associated with unproductive binding to lignin.